Antibiosis and antixenosis resistance of collard genotypes to Bemisia tabaci MEAM1 (Hemiptera: Aleyrodidae) - Baldin, Edson L. L. [UNESP]; Domingos, Georgea M. [UNESP]; Bentivenha, José P. F.; Canassa, Vinícius F. [UNESP]; Lourenção, André L. (Springer Nature, 2022)
Bemisia tabaci (Genn.) MEAM1 (Middle East-Asia Minor) (Hemiptera: Aleyrodidae) is an important pest of collards, Brassica oleracea var. acephala. This insect reaches high levels of infestation in the field, causing direct damage to plants, compromising productivity. Concerns related to chemical control have resulted in a search for alternative methods to manage populations of B. tabaci in the field. The use of resistant genotypes is a potentially and a valuable strategy to manage this insect, reducing its populations below the level at which it causes economic damage. This work evaluated period of incubation, duration of each instar, nymphal period, nymphal survival, development egg-adult, and adult longevity of B. tabaci MEAM1 on 13 collard genotypes under laboratory conditions after a previous screening involving 32 genotypes for oviposition non-preference. The following parameters were determined: duration period per instar, total nymphal period, nymphal survival, total development period (egg-adult) and adult longevity. The genotypes P1C, MG and LG expressed antibiosis and/or antixenosis against B. tabaci MEAM1, prolonging the total development period (egg-adult) of the insect. IMAN W, MOP and VE reduced the nymphal survival of the whiteflies, indicating some potential for resistance. Due to the importance of collards cultivation and the substantial damage potential that this insect presents to the crop, the selection of resistant genotypes is promising and may represent a useful tool for the management of whitefly in crops. Our results will contribute to genetic improvement programs for brassicas focusing on resistance to B. tabaci MEAM1.
Keywords: Brassica oleracea var. acephala; Host plant resistance; Whitefly